THE APPLICATION OF ARCHITECTURE BAHAVIORAL STUDIES FOR DESIGN STRATEGY IN FEMALE STUDENT’S DORMITORY IN SLEMAN - Fauzi, Iqbal Maulana; Samsudi, Samsudi; Wahyuwibowo, Agung Kumoro (ARSITEKTURA, 2018)
Nowadays, education is such a global priority and because of it, it is necessary for citizen to continue their education from Senior High School to Higher Education stage. Special Region of Yogyakarta is one of the most favorite destination to continue higher education. According to some researches in 2015, 70% of new university students came from outside Yogyakarta. Since there are so many students from outside Yogyakarta, the demand of student housing grows higher, especially for female students. A housing for students who came from outside Yogyakarta is necessary. This housing can be used as temporary place to live when they continue their study, while it also can support the student’s self-development in academic or non-academic activity. There are so many options of housing for female students, but a dormitory is the best option. A dormitory is the best option of housing for female students that can be provided with self-development facilities in academic or non-academic activity. This dormitory will be designed in a good way, so the female students as the user could get comfortable, motivated, and optimal in developing themselves. This dormitory also has to provide a serenity and comfort while the students doing their activity. In order to get those criteria, a study about behavioral architecture should be applied as a design approach. The studies of behavioral architecture that will be applied in design strategy are spatial analysis, site analysis, mass composition analysis, structure system and material analysis, and utility system. The analysis process that apply architecture behavioral study can give a result of dormitory design which give comfort when the user living and doing self-development activity.